Resilience and the dissemination of flood disaster early warning messages in a township in South Africa - Raphela, Tlou D.; Ekeke, N. (Frontiers in Communication, 2025)
Disaster early warning systems are regarded as one of the key activities in the implementation of both disaster preparedness and response measures. The need to implement effective disaster early warning systems in Africa, in particular, dates back to the early nineties. Even before the UN Sendai conference, initiatives to improve existing early warning systems had already been identified. This study assessed flood resilience based on the dissemination of Early Warning Messages in Vosloorus Township. The study applied a quantitative approach by collecting data using a structured questionnaire and applying inferential statistics to analyse the data from 100 participants of two informal settlements of Vosloorus Extension 21 with a combined population size of 251. The study applied a series of one-way ANOVA tests separately, two separate General Linear models and one ordinal regression on R statistical software to address the objectives of this study. The study results showed the significant role that demographic characteristics play in shaping the understanding of disasters within the study community. These factors contribute to the community’s resilience, particularly in the dissemination of early warning messages. There appears to be a disconnect in translating this awareness into effective understanding and action based on EWMs. This disconnect may be related to how information is communicated and the general preparedness of the community. For communities where cellphone ownership is limited, alternative methods of delivering EWMs should be considered to ensure broader and more equitable access to crucial information. Addressing infrastructural issues such as electricity and internet access is also essential to improve the timeliness and efficiency of early warning systems.